Vaccines against RNA Viruses - Saiz, Juan Carlos (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
RNA viruses cause animal, human, and zoonotic diseases that affect millions of individuals, as is being exemplified by the devastating ongoing epidemic of the recently identified SARS-Cov-2. For years vaccines have had an enormous impact on overcoming the global burden of diseases. Nowadays, a vast number of different approaches, from purified inactivated and live attenuated viruses, nucleic acid (DNA or RNA) based candidates, virus-like particles, subunit elements, and recombinant viruses are been employed to combat viruses. However, for many of them efficient vaccines are not yet available. This will probably change dramatically with the current Covid-19 pandemic, as a vast variety of vaccinology approaches are being tested against it, with hundreds of candidates under development, dozens of them already in clinical trials, a fact that is breaking records in vaccine development and implementation. This is becoming possible thanks to the enormous work carried out during years to have the bases for a quick response, even against unknown pathogens, in an impressive short time. Here, results obtained with different vaccine´s methodological approaches against human (HIV, HCV, HRV) animal (PRRSV, PEDV, FMDV, VHSV) and zoonotic (RVF, WNV), RNA viruses are presented by field experts.